Optimizing AI for Competitive Growth at Digital Marketing Agencies in Indonesia - Demetrio Jesu (Journal of Economics and Business UBS, 2026)
Artificial intelligence (AI) has increasingly transformed digital marketing practices by supporting content creation, data analysis, reporting, campaign preparation, creative production, and service innovation. However, the adoption of AI does not automatically lead to optimal business outcomes. This study examines how Indonesian digital marketing agencies adopt and optimize AI for competitive growth. Using a qualitative multiple case study approach, this research analyzes three digital marketing agencies in Indonesia: Socioworks, IND! Communication, and Pepple Digital. Data were collected through semi-structured interviews with agency owners, managers, and decision-makers, supported by digital observation and secondary data. The data were analyzed using the Gioia Method and interpreted through the Technology Acceptance Model (TAM) and the Technology-Organization-Environment (TOE) framework. The findings show that AI adoption is mainly driven by operational efficiency, competitive pressure, and business growth opportunities. However, AI optimization is constrained by human capability gaps, generic AI outputs, fragmented workflows, tool integration barriers, and unclear cost-performance measurement. The study concludes that AI can support competitive growth only when agencies move beyond basic task-based AI usage toward structured, integrated, and client-value-oriented AI optimization. The proposed business solutions include AI capability development, strategic AI investment and governance, workflow optimization, service innovation, and AI-assisted service packaging.